2020
DOI: 10.1371/journal.pone.0229770
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to access to the Norwegian healthcare system among sub-Saharan African immigrant women exposed to female genital cutting

Abstract: Introduction Millions of women and girls have been exposed to female genital cutting (FGC). The practice of FGC extends beyond countries in Africa and Asia in which it is traditionally practiced. Women living with FGC in Norway have been reported to be in need of healthcare, but there is evidence of suboptimal use of healthcare services among this group, and we lack the women's perspective about this problem. This study aims to explore the experiences and perceptions hindering access and use of the Norwegian h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In a previous study, women who have undergone FGM are faced with lack of specialized understanding of their health needs and also being treated by male healthcare providers may cause discomfort [ 26 ]. Other scholars have indicated that breach of privacy and confidentiality within the healthcare setting hinders FGM victims' utilisation of maternal health services of which SBA is a major component [ 27 , 28 ]. Due to the prohibition of FGM in countries in SSA such as Kenya, Nigeria, Guinea, Liberia, and Burkina Faso among others, FGM victims fear their status can cause arrest and legal actions against their relatives, hence, their preference not to seek health services including SBA [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, women who have undergone FGM are faced with lack of specialized understanding of their health needs and also being treated by male healthcare providers may cause discomfort [ 26 ]. Other scholars have indicated that breach of privacy and confidentiality within the healthcare setting hinders FGM victims' utilisation of maternal health services of which SBA is a major component [ 27 , 28 ]. Due to the prohibition of FGM in countries in SSA such as Kenya, Nigeria, Guinea, Liberia, and Burkina Faso among others, FGM victims fear their status can cause arrest and legal actions against their relatives, hence, their preference not to seek health services including SBA [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that in the first stage of their healthcare-seeking journey, the participants' health problems they identified as candidates for medical attention were: lumps and other genitourinary, sexual, and mental health problems that persisted, interfered with their ability to perform expected duties and roles, or caused severe pain. Dissimilar to participants in a former study [45], most of our participants had received information on FGC-related problems and thus suspected their health problems could be FGC-related. A possible explanation for this difference could be that other immigrant groups included in the before mentioned study are less targeted with such information than Somali and Sudanese [53], who were the only groups we included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We also know that some girls find premarital deinfibulation unacceptable because it contradicted some sexual and cultural norms [42][43][44]. A very recent study [45] gave new insights on other barriers to help-seeking and access to healthcare that 13 girls and women subjected to FGC had experienced in Norway. Identified barriers included lack of information on both FGC-related health complications and healthcare services, avoidance of disclosing FGC-related health problems to healthcare providers because of shyness and shame, insufficient knowledge of FGC among healthcare providers, and healthcare providers being more concerned about the criminal aspects of FGC than the women's healthcare needs.…”
Section: Plos Onementioning
confidence: 99%
“…While defibulation is often portrayed as "easy to perform" and as not requiring particular surgical skills in plastic and reconstructive surgery [54], HCPs report uncertainty regarding how to defibulate. Furthermore, defibulated women reported distress and stigma for having "ugly" (post-defibulation) genitals, with the "flesh…hanging" [55]. Without proper communication about the physical and social issues of defibulation, as well as a requirement that operating HCPs have sufficient reconstructive surgical skills, women may be reluctant to opt for defibulation.…”
Section: Controversy Regarding Timing Of Defibulation -Premarital Vs ...mentioning
confidence: 99%